2000
DOI: 10.1073/pnas.100101797
|View full text |Cite
|
Sign up to set email alerts
|

Effective inhibition of human cytomegalovirus gene expression and replication by a ribozyme derived from the catalytic RNA subunit of RNase P from Escherichia coli

Abstract: A sequence-specific ribozyme (M1GS RNA) derived from the catalytic RNA subunit of RNase P from Escherichia coli was used to target the overlapping exon 3 region of the mRNAs encoding the major transcription regulatory proteins IE1 and IE2 of human cytomegalovirus. A reduction of more than 80% in the expression levels of IE1 and IE2 and a reduction of about 150-fold in viral growth were observed in human cells that stably expressed the ribozyme. In contrast, a reduction of less than 10% in the IE1͞IE2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
174
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(176 citation statements)
references
References 35 publications
2
174
0
Order By: Relevance
“…M1 RNA may be converted to an endoribonuclease that specifically cleaves other RNAs through the covalent attachment of a guide sequence (GS) which is complementary to the target RNA and to the 39 end of the M1 RNA. Reduced levels of virus replication of herpes simplex virus (Trang et al, 2000a) and cytomegalovirus (Trang et al, 2000b) in cell culture have been reported with the use of M1GSs.…”
mentioning
confidence: 98%
“…M1 RNA may be converted to an endoribonuclease that specifically cleaves other RNAs through the covalent attachment of a guide sequence (GS) which is complementary to the target RNA and to the 39 end of the M1 RNA. Reduced levels of virus replication of herpes simplex virus (Trang et al, 2000a) and cytomegalovirus (Trang et al, 2000b) in cell culture have been reported with the use of M1GSs.…”
mentioning
confidence: 98%
“…We constructed functional ribozyme M1-A by linking the 3′ terminus of M1 RNA with a guide sequence of 18 nucleotides that is complementary to the targeted M80.5 mRNA sequence. Control "inactive" ribozyme M1-B was constructed to contain the same guide sequence and derived from C102 RNA, an M1 mutant that contained point mutations at the active P4 domain abolishing its catalytic activity (9). To determine if M1GS ribozyme with an incorrect guide sequence could affect the level of the target mRNA, ribozyme M1-TK1, which was derived from M1 RNA and targeted the HSV-1 thymidine kinase (TK) mRNA (9), was also used in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Control "inactive" ribozyme M1-B was constructed to contain the same guide sequence and derived from C102 RNA, an M1 mutant that contained point mutations at the active P4 domain abolishing its catalytic activity (9). To determine if M1GS ribozyme with an incorrect guide sequence could affect the level of the target mRNA, ribozyme M1-TK1, which was derived from M1 RNA and targeted the HSV-1 thymidine kinase (TK) mRNA (9), was also used in the analysis. We observed in vitro cleavage of an M80.5 mRNA substrate by M1-A, but not M1-B or M1-TK1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations